Sufi symbolism of the beloved and the sea in Ahmadun Yosi Herfanda’s poetry: A perspective of Braginsky’s theory - Sujarwoko Sujarwoko; Suhartono Suhartono; Marista Dwi Rahmayantis (Universitas Muhammadiyah Malang, 2026)
Studies on Sufi poetry indicate that symbolism functions not only as an aesthetic expression but also as a medium of complex spiritual experience. However, previous research often separates religious symbols from existential imagery, resulting in fragmented interpretations of meaning. This study aims to analyze the symbols of the Beloved and the sea in the poetry of Ahmadun Yosi Herfanda using a Sufi symbolic approach. This research employs a qualitative method of textual analysis grounded in Vladimir Braginsky's symbolic-Sufi framework. The data consist of selected poems analyzed through symbol identification, interpretation of meaning, and their relation to Sufi concepts. The findings reveal that the Beloved's symbol represents the ultimate goal of union with the Divine. At the same time, the sea symbolizes the spiritual journey characterized by longing, trials, and alienation. Both symbols are integrated into a unified mystical structure connecting journey and union. The study concludes that mystical experience in Ahmadun Yosi Herfanda’s poetry is integrative and multidimensional. Its scholarly contribution lies in developing a Sufi symbolic reading that combines relational (Beloved) and processual (sea) dimensions within a systematic analytical framework.